PENGARUH BANTUAN SOSIAL BADAN PENYELENGGARA JAMINAN SOSIAL KETENAGAKERJAAN TERHADAP KESEJAHTERAAN MASYARAKAT BOYOLALI TAHUN 2021 - Andhika Wahyu Christian; Muhammad Cholis; Suprihati Suprihati (JURNAL ILMIAH EDUNOMIKA, 2022)
The purpose of this study was to determine the effect of the amount, flow, and target of BPJS Employment Wage Subsidy Beneficiaries (BSU) on the welfare of the Boyolali community in 2021 (Case Study of Jurug Village, Mojosongo District). The research method is descriptive with a quantitative approach. The research location is in Jurug Village, Tamansari District, Boyolali Regency, the research population is 100 people registered in BPJS Employment and a sample of 50 people using purposive aampling method. Data obtained from surveys, collected and processed using SPSS 2.1 for windows. The result of the research is that the amount and flow of the BPJS Employment Wage Subsidy (BSU) have a significant effect on Community Welfare. The target of the BPJS Wage Subsidy Assistance (BSU) has no significant effect on the welfare of the community. Keywords : Bantuan Subsidi Upah (BSU) BPJS Social Allocation, BSU recipient communities, Community Welfare.